2000
DOI: 10.1046/j.1440-1630.2000.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner‐researchers in occupational therapy

Abstract: Few occupational therapy clinicians are research productive even though their involvement in research is encouraged. The role of ‘research‐practitioner’ is put forward as a means by which practitioners can be research productive. There is, however, an absence of studies exploring experience of the minority of practitioners who do produce research. This study used a qualitative approach to do this in occupational therapy. Purposive sampling was conducted of all research productive clinicians in acute‐care hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…This perceived importance facilitated the participants' interest in and intent to be involved in research, but, similarly, many barriers were described that influenced their use and production of research in the clinical environment. In Australia, Cusick and her colleagues have investigated clinicians' (including managers') views on research more broadly (Cusick et al, 1999;Cusick, 2000Cusick, , 2001. This research supports the findings of the international studies cited above, and further extends our understanding by investigating the experiences of clinicians who are active and productive in research.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…This perceived importance facilitated the participants' interest in and intent to be involved in research, but, similarly, many barriers were described that influenced their use and production of research in the clinical environment. In Australia, Cusick and her colleagues have investigated clinicians' (including managers') views on research more broadly (Cusick et al, 1999;Cusick, 2000Cusick, , 2001. This research supports the findings of the international studies cited above, and further extends our understanding by investigating the experiences of clinicians who are active and productive in research.…”
Section: Introductionsupporting
confidence: 56%
“…As a result, treatment effectiveness and outcome studies have been identified as key issues for the profession (Llorens and Gillette, 1985;Llorens and Snyder, 1987;Law, 1989a;Taylor and Mitchell, 1990;Timmerman et al, 1994;Unsworth, 2000). Active involvement of clinicians in clinical research has been advocated to facilitate professional practice that is grounded in theory and research, and provides quality care to our clients (Baum et al, 1984;Llorens and Gillette, 1985;Mitcham, 1986;Llorens and Snyder, 1987;Cusick, 1987Cusick, , 1994Cusick, , 2000Law, 1989a;Taylor and Mitchell, 1990;Rogers and Holm, 1994;Timmerman et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11, No. 2;2015 253 Cusick, 2000Cusick, , 2001Watts, 2009), doctoral research practice in professional-service fields such as sport pedagogy , and post-PhD professional research roles (e.g., Åkerlind , 2005Pelz & Andrews, 1976). …”
Section: Occupational Socialization To Researcher Rolesmentioning
confidence: 99%
“…Broadly, researcher role development is conceived as a loose iterative process commencing with: (a) a person identifying a particular role as desirable; (b) engaging in activities and building relationships to develop the role in their lives; and (c) evaluating whether or not role acquisition was successful or a good life "fit" using feedback from their interactions with others and measures of career achievement (e.g., Cusick, 2000Cusick, , 2001. Although there is some directionality in role development, it is not a linear process because individuals go back and forth reflecting on their evolving identity in changing social contexts.…”
Section: The Personal Biographymentioning
confidence: 99%